Taxonomic key of nymphs of Ephemeroptera (Insecta) from southeastern Peru - Miñano, Pablo (2019)
Ephemeroptera is an insect order of whose immature stages play an important ecological role in aquatic ecosystems. However, its diversity knowledge in tropical areas is scarce. In particular, only 64 species of 35 genera and eight families have been reported in Peru. In this work, we provide a general key of Ephemeroptera nymphs for southeastern Peru. Nymphs were collected from streams of Cusco and Madre de Dios departments, within an altitudinal gradient of 180 – 4411 m, in 2012, 2013, 2015 and 2017 years. The samples were obtained by manual collection, using a Surber net and by colonization of leaf packs. We recognized 48 genera within eight families, coming from 36 streams within the gradient. Six genera are new records to Peru: Prebaetodes, Zelusia, Meridialaris, Tricorythopsis, Homoeoneuria and Hubbardipes.